Development of Power Electronic Circuits Database for Knowledge-Based System - Yousef Zahran, Ahmad Dib (2000)
The development of design automation tools for a power electronic circuit has received a great deal of attention in the last two decades. To provide an optimum solution for each power electronics application demands the selection of the most appropriate power electronic devices, power circuit and control philosophy. For a certain applications, it must be decided which power circuit topology and which power semiconductor with which control strategy is best suited for it. Their design and fabrication require extensive knowledge and sophistication, that must be continually updates as the technologies improve. Considerable engineering effort and knowledge are required to take a power circuit from a laboratory prototype to a finished product. Other than being an expert in areas as diverse as thermal design, circuit and system packaging, circuit protection, and safety and electromagnetic interference regulations. With such a highly demanding expertise required of power electronic circuits' designers and with such rapid advancements in the field of circuit topology and semiconductor devices it is difficult for designers to come up with an optimum circuit and the right device within a short time. These difficulties can be solved using a design-aided system with high accuracy and flexibility in a short time. In this study the developed system is named PEDAS (Power electronic Design Aid System). The system is characterized as an intermediate object-oriented system that allows the user to deal with different software packages through an attractive interface. The aim of this research is to develop a database circuits library. The implementation includes generation of formatted files to be used as input streams with the design packages, writing an interface program for each kind of these software, and managing the data flow timing and dependency among them. In this thesis the circuit topology data base development based on PSPICE is presented with examples of converters and inverters circuits. The database circuits library was designed and used successfully by some of the researchers of the electrical engineering department in the Control and Automation System Center.